Cow urine as an organic nutrient source for hydroponic vegetable production - I Putu Sujana; Luh Putu Yuni Widyastuti; Ni Kadek Ema Sustia Dewi (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Fermented cow urine (cow bio urine) is used as an organic source of nutrients. This study aimed to determine the effect of various concentrations of cow bio urine as the organic nutrient source on the growth and yield of vegetable crops in hydroponic systems.Method: Research was conducted in a greenhouse at the University Farm from November 2020 to January 2021 with a split plot in RCBD. The main plot consisted of 3 vegetables (bok choy, spinach, and water spinach). The subplot had 5 concentrations prepared by mixing cow bio urine with distilled water at C1: 10%, C2: 20%, C3: 30%, C4: 40%, and C5: 50%. These solutions were used as hydroponic nutrient solutions. All the treatment combinations were maintained in 4 replications.Results: Cow urine analysis before and after fermentation revealed an increase in nutrient content. The highest plant growth and yield were obtained in all three vegetables at the concentration of 50% cow bio urine. Maximum leaf number, leaf area, foliage dry weight, root dry weight, total dry weight, and foliage fresh weight were significantly higher in the above treatment. The highest foliage fresh weight was observed in treatments with 50% cow bio urine, with values of 57.02 g (bok choy), 54.97 g (spinach), and 26.29 g (water spinach).Conclusion: Cow bio urine could be effectively used as a hydroponic nutrient solution to grow organic vegetables. The regression showed that the optimal concentration of cow bio urine might be higher than the present levels.